Strategies and Challenges in the Distribution of Public Health Centre Doctors in Indonesia - Tambun, Sondang Whita Kristina; Bashabih, Masyitoh; Zakaria, Zakaria (Poltekkes Kemenkes Palu, 2024)
Adequacy of doctors through the deployment of public health center doctors to achieve equity in health services for the community. The deployment of public health center doctors has been implemented through various policies but there are still public health centers that do not have a doctor. This article aims to determine the strategies, challenges, and successes in the distribution of public health center doctors. Document analysis of legal documents was approached using the READ method to determine the distribution strategy of doctors. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol from two online database search engines, where 25 articles were found that met the research objectives, inclusion, and exclusion criteria. The challenges of the distribution of public health center doctors are due to deployment for remote and very remote areas. Factors that challenge the distribution of doctors are individual factors, work factors, living environment factors, and health system factors. Recruitment and deployment of public health center doctors in remote areas need to be done comprehensively with crossector.